Strategi Pembinaan Melalui Project Citizen dalam Rangka Penguatan Self Confidence dan Creative Skill Peserta Didik - Sofianto, Rahadian; Untari, Sri; Kusumaningrum, Shirly Rizki (University of Muhammadiyah Malang, 2024)
Pancasila education in the independent curriculum is designed to build various personal and interpersonal student competencies. Learning must provide students with a challenging, fun, and meaningful learning experience. The selection of learning models based on the subject matter students learn is essential. With a qualitative approach, this research was carried out at SDN Sambi 1 Ringinrejo District to strengthen students' self-confidence and creative skills. This research was carried out with the research subjects of grade 5 students. The informants of this study were the principal, teacher and 6 learners. This is because, based on information from teachers, these students tend to be less active in learning and shy about conveying their ideas or ideas. Data were collected through observation, interviews and documentation and analyzed using a four-step process: data reduction, analysis, presentation, and conclusions. The results of this study show that the right strategy to strengthen self-confidence and creative skills is to apply the project citizen learning model, whose learning steps include identifying problems that exist in society, selecting problems as the focus of class studies, collecting information from various resource persons, portfolio development, and reflection. The results showed a correlation between applying the project citizen learning model and strengthening students' self-confidence and creative skills. Collecting information, group discussions, and preparing portfolios foster students' creative skills to create and solve problems that arise in everyday life, especially those related to the application of Pancasila values that occur in society.